TOTAL BACTERIA IN VARIOUS AGES AND LOCATIONS OF BALI CATTLE IN NUSA PENIDA - mantrawan, chyntia nirmalasari; Besung, I Nengah Kerta; Suarjana, I Gusti Ketut; Suwiti, Ni Ketut (Buletin Veteriner Udayana, 2018)
This study aims were to determine the total number of bacteria at maturity level and farm locations. As many as 24 catlle fecal samples were examined using the casting method. This study used a Randomized Complete Block Design of 2 x 3 factorial consist of  two farm locations (highlands and lowlands) and  three levels of cattle maturity (calves, heifers, adult). The total bacteria were analyzed using Analysis of Variance and continued by Least Significant Difference Test. The results of the total number bacteria isolated from feces adult 724.6250 x 10 9 CFU/g higher than heifers 667.5000 x 10 9 CFU/g and calf 499.5000 x 10 9 CFU/g. Total number of bacteria isolated from feces of bali cattle from highland 629.4167 x 10 9 CFU/g is not showed significant different compare to bali cattle from lowland 631.6667 x 10 9 CFU/g.